2001
DOI: 10.1001/archpsyc.58.5.503
|View full text |Cite
|
Sign up to set email alerts
|

A 33-Year Follow-up of Narcotics Addicts

Abstract: While the number of deaths increased steadily over time, heroin use patterns were remarkably stable for the group as a whole. For some, heroin addiction has been a lifelong condition associated with severe health and social consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
512
4
15

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 737 publications
(554 citation statements)
references
References 10 publications
23
512
4
15
Order By: Relevance
“…39 While poisoning accounted for 40.9% of deaths in our study, it was the cause of 22% of the deaths in a 33-year study of heroin users. 40 A longitudinal intervention study of mortality after drug treatment found the same three leading causes of death: poisoning, trauma, and medical illness. 37 Heroin as primary drug of choice is a major focus in the addiction mortality literature because of the high risk of overdose and infectious disease associated with its use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 While poisoning accounted for 40.9% of deaths in our study, it was the cause of 22% of the deaths in a 33-year study of heroin users. 40 A longitudinal intervention study of mortality after drug treatment found the same three leading causes of death: poisoning, trauma, and medical illness. 37 Heroin as primary drug of choice is a major focus in the addiction mortality literature because of the high risk of overdose and infectious disease associated with its use.…”
Section: Discussionmentioning
confidence: 99%
“…37 Heroin as primary drug of choice is a major focus in the addiction mortality literature because of the high risk of overdose and infectious disease associated with its use. 4,15,17,18,40,41 Homelessness is another predictor of risk of death for substance-dependent people. [19][20][21] Of note, any homelessness was not a significant risk factor in our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…There is no accepted definition of ‘injecting risk’, with studies showing high rates of relapse after 1 year but reducing substantially after more than 5 years 40, 41. By including all individuals who reported ever injecting, it is conceivable that we have included some who have ceased injecting, which would lead to an overestimate.…”
Section: Discussionmentioning
confidence: 99%
“…The use of heroin among high school seniors in the United States has also increased (Monitoring the Future Study, 2000). Many heroin-dependent individuals also abuse cocaine, marijuana, and alcohol (Hser et al, 2001). These substance abusers are at risk for many medical problems, including collapsed veins, endocarditis, abscesses, cellulitis, hepatitis, pneumonia, lymphadenopathy, spongiform leukoencephalopathy, and HIV/AIDS (Ben Diane et al, 2000;Hser et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Many heroin-dependent individuals also abuse cocaine, marijuana, and alcohol (Hser et al, 2001). These substance abusers are at risk for many medical problems, including collapsed veins, endocarditis, abscesses, cellulitis, hepatitis, pneumonia, lymphadenopathy, spongiform leukoencephalopathy, and HIV/AIDS (Ben Diane et al, 2000;Hser et al, 2001). Treatment approaches such as methadone, l-a acetomethadol, and buprenorphine, which are useful in reducing heroin use and in keeping patients in treatment programs (O'Connor and Fiellin, 2000;Johnson et al, 2000), might reduce health risks in these patients.…”
Section: Introductionmentioning
confidence: 99%